Hubungan kepatuhan antenatal care dengan pemilihan penolong persalinan di Kabupaten Natuna - Sri Juana; Detty Siti Nurdiati; Atik Triratnawati (Berita Kedokteran Masyarakat (BKM), 2016)
Compliance of antenatal care and election of birth helpers in NatunaPurposeThis study aimed to determine the association of ANC (Antenatal care) compliance with birth attendant choice in Natuna.MethodsThis study used a cross-sectional method. The subjects of the research were mothers in Natuna regency 2014. The variables were: independent variable (ANC compliance), the dependent variable (the birth attendant choice), and the control variables (age, maternal education, distance to the health facilities, parity). Data collection used questionnaires and interviews. The data analysis used descriptive and inferential analysis. The bivariable analysis used the chi-square test and multivariable analysis used logistic regression test with 95% of confidence interval (CI) and a significance level of p <0.05.ResultsBivariable and multivariable analysis showed significant correlations between ANC compliance with birth attendant choice. Pregnant women who did not comply doing ANC according to the standard that has been set at least four times had a chance two times more likely to give birth with the traditional birth attendant (TBA) than the pregnant women who complied to implement the ANC during pregnancy. Mothers with low education had a chance two times greater of choosing the TBA as birth attendant than women who are highly educated. Mothers with parity of >2 had a chance 1.9 times greater of choosing the TBA as birth attendant than women with parity ≤2.ConclusionsThere needs to be a control program from the health department working with community health workers to socialize awareness of the importance of the ANC. There needs to be the addition of TBA who are trained and partnered especially in remote areas because it cannot be denied there are still many people who choose TBA as a birth helper.